Online teaching going massive: input and outcomes. (1st June 2016) - Leire, Charlotte; McCormick, Kes; Richter, Jessika Luth; Arnfalk, Peter; Rodhe, Håkan
Abstract: The proliferation of massive open online courses is a recent phenomenon in higher education. At the International Institute for Industrial Environmental Economics at Lund University in Sweden, emerging pedagogical approaches in e-learning have long been embraced, allowing for valuable experience with new educational technologies applied in education for sustainability. In 2014, the Institute was given a formal task to develop a massive open online course on "Greening the Economy: Lessons from Scandinavia", thereby utilizing existing capacities and experiences while experiencing new challenges revealed by courses of larger scale. This article presents the background to the Institute's undertaking with massive open online courses and the range of expectations from the main stakeholders. The article discusses massive open online courses as a novel venue for e-learning in sustainability education as regards learning activities, design and content. It concludes that while the initial experience of such a course has been positive, in order to better cater to the learner groups, continued attention needs to be paid to course design, teacher capacity and in particular an examination of learner motivations. Highlights: The MOOC "Greening the Economy: Lessons from Scandinavia" was launched in 2015. Learning activities for MOOCs need to be different from traditional online courses. Stakeholder expectations for the MOOC were met. Continuous learning and adaptation among teachers is crucial for e-learning. Learner motivation is likely to impact course success.